A novel transition protocol to post-quantum cryptocurrency blockchains - Almuhammadi, Sultan; Alghamdi, Sarah (Frontiers in Computer Science, 2025)
Blockchain-based public ledgers, known as cryptocurrencies, are used to build peer-to-peer digital payment systems. Cryptocurrency transactions are secured by digital signatures. However, today's public-key cryptography, which is the basis of digital signatures, is vulnerable to quantum attacks. Therefore, there is a significant risk to the 2.7 trillion dollar market capitalization of the cryptocurrency sector in the Quantum Era. In this paper, we review the current risk of quantum attacks on the blockchains of cryptocurrencies. We also discuss the migration of existing cryptocurrencies from classical to quantum-resistant blockchains and review some of the existing transition protocol algorithms. The main contribution of this work is to propose a new transition protocol algorithm that allows smooth and safe migration to post-quantum blockchains without delay. The proposed algorithm requires a soft fork of the original blockchain, which makes it more desirable than other hard-fork solutions. We also prove the soundness and completeness properties of the proposed algorithm and discuss its advantages compared to the existing ones. We conclude by highlighting our recommendations based on this study.